The Modification of Regulatory Circuits Involved in the Control of Polyhydroxyalkanoates Metabolism to Improve Their Production - Velázquez-Sánchez, Claudia; Espín, Guadalupe; Peña, Carlos; Segura, Daniel (Frontiers in Bioengineering and Biotechnology, 2020)
Poly-(3-hydroxyalkanoates) (PHAs) are bacterial carbon and energy storage compounds. These polymers are synthesized under conditions of nutritional imbalance, where a nutrient is growth-limiting while there is still enough carbon source in the medium. On the other side, the accumulated polymer is mobilized under conditions of nutrient accessibility or by limitation of the carbon source. Thus, it is well known that the accumulation of PHAs is affected by the availability of nutritional resources and this knowledge has been used to establish culture conditions favoring high productivities. In addition to this effect of the metabolic status on PHAs accumulation, several genetic regulatory networks have been shown to drive PHAs metabolism, so the expression of the PHAs genes is under the influence of global or specific regulators. These regulators are thought to coordinate PHAs synthesis and mobilization with the rest of bacterial physiology. While the metabolic and biochemical knowledge related to the biosynthesis of these polymers has led to the development of processes in bioreactors for high-level production and also to the establishment of strategies for metabolic engineering for the synthesis of modified biopolymers, the use of knowledge related to the regulatory circuits controlling PHAs metabolism for strain improvement is scarce. A better understanding of the genetic control systems involved could serve as the foundation for new strategies for strain modification in order to increase PHAs production or to adjust the chemical structure of these biopolymers. In this review, the regulatory systems involved in the control of PHAs metabolism are examined, with emphasis on those acting at the level of expression of the enzymes involved and their potential modification for strain improvement, both for higher titers, or manipulation of polymer properties. The case of the PHAs producer Azotobacter vinelandii is taken as an example of the complexity and variety of systems controlling the accumulation of these interesting polymers in response to diverse situations, many of which could be engineered to improve PHAs production.